1993
DOI: 10.1007/bf00173489
|View full text |Cite
|
Sign up to set email alerts
|

Influence of intravenously administered lidocaine on cerebral blood flow in a baboon model standardized under controlled general anaesthesia using single-photon emission tomography and technetium-99m hexamethylpropylene amine oxime

Abstract: The baboon under general anaesthesia as a model to assess drug-induced cerebral blood flow changes (delta CBF) using single-photon emission tomography (SPET) offers great in vivo possibilities but has to comply with demands on control of anaesthesia-related influencing factors, such as PaCO2 changes. The model sought in this study and described here allows control of PaCO2, in the baboon under thiopentone anaesthesia by ventilation, and was evaluated for the functional dependence of delta CBF vs delta PaCO2, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Thus, direct vascular effects, typically removed by normalization, appear not to play a major role in procaine regional responses. Dormehl et al (1993) has reported that baboons administered lidocaine (6 mg/kg) intravenously exhibited an increased in rCBF (with SPECT) that was associated with changes in PaCO 2 , suggesting that changes in cerebrovascular autoregulation may have contributed to lidocaine-induced neural activation. In addition, Usubiaga et al (Usubiaga et al, 1967) observed a marked fall in systolic and diastolic blood pressure following lidocaine infusion (5-10mg) but not following procaine (10-20mg).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, direct vascular effects, typically removed by normalization, appear not to play a major role in procaine regional responses. Dormehl et al (1993) has reported that baboons administered lidocaine (6 mg/kg) intravenously exhibited an increased in rCBF (with SPECT) that was associated with changes in PaCO 2 , suggesting that changes in cerebrovascular autoregulation may have contributed to lidocaine-induced neural activation. In addition, Usubiaga et al (Usubiaga et al, 1967) observed a marked fall in systolic and diastolic blood pressure following lidocaine infusion (5-10mg) but not following procaine (10-20mg).…”
Section: Discussionmentioning
confidence: 99%
“…In the range of PaCO 2 from 20 to 80 mmHg, the cerebral blood flow increases by about 2 ml/min/100g of brain tissue for every 1 mmHg increase in PaCO 2 . This increase of CBF is the result of cerebral vasodilation, mainly mediated through changes in extracellular pH (Dormehl et al, 1993;Golding et al, 1999;Giardino et al, 2007). Rat studies have shown that the relationship between PaCO 2 and CBF can be represented in a sigmoid graph with two plateaus, one below 25 mmHg and another above 75 mmHg.…”
Section: Partial Arterial Carbon Dioxide Pressure (Paco 2 ) and Cereb...mentioning
confidence: 99%
“…The most important difference in veterinary medicine is the need for anesthesia for these procedures, which may influence the measurement of cerebral blood flow (CBF). Indeed, CBF changes have been clearly demonstrated after the administration of different anesthetics in man and in different animal species, including dogs, primates and rabbits (Morita et al, 1977;Roald et al, 1986;Yeh et al, 1988;Karlsson et al, 1990;Zornow et al, 1990;Lutz et al, 1991;Van Aken and Van Hemelrijck, 1991;Dormehl et al, 1993;Werner, 1995;McPherson et al, 1997;Ohata et al, 1999;Nagase et al, 2003).…”
Section: Introductionmentioning
confidence: 99%